1999
DOI: 10.1159/000006913
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein in Dilated Cardiomyopathy

Abstract: The prognosis for patients with idiopathic dilated cardiomyopathy (DCM) is poor, although clinical features are variable. Prediction of outcome has been difficult in individual patients based on laboratory data. In some patients with DCM, myocardial damage secondary to viral or immune-mediated myocardial inflammation may persist. To objectively assess inflammation, we measured plasma concentrations of C-reactive protein (CRP) in 188 patients with idiopathic DCM over 5–8 years. All had dyspnea and fatigue at re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(60 citation statements)
references
References 20 publications
(19 reference statements)
7
49
0
2
Order By: Relevance
“…Lamblin et al confirmed the prognostic value of hs-CRP for adverse cardiac events only in patients with HF of ischemic etiology [30]. Other authors found a strong correlation between hs-CRP levels and poor prognosis also in non-ischemic dilated cardiomyopathy [31,32].…”
Section: Depression and Inflammationmentioning
confidence: 91%
“…Lamblin et al confirmed the prognostic value of hs-CRP for adverse cardiac events only in patients with HF of ischemic etiology [30]. Other authors found a strong correlation between hs-CRP levels and poor prognosis also in non-ischemic dilated cardiomyopathy [31,32].…”
Section: Depression and Inflammationmentioning
confidence: 91%
“…Heart failure is characterized by activation of pro-inflammatory cytokines TNF-a and IL-6 and elevation of C-reactive protein [5,6]. C-reactive protein is an acute-phase protein which, due to its binding specificity for phosphocholine present in a large variety of molecules, recognizes a range of pathogenic targets including membranes of apoptotic and reactive cells [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, these cytokines are elevated in patients with other cardiomyopathies. As this inflammatory marker is associated with adverse prognosis in patients with idiopathic dilated cardiomyopathy [5,6,11], we investigated whether levels of plasma C-reactive protein and IL-6 at baseline could predict clinical outcome in patients with PPCM. In chronic heart failure, low levels of total cholesterol have been found to be a predictor of impaired survival.…”
Section: Introductionmentioning
confidence: 99%
“…(25) CRP is an acute-phase protein which recognizes a range of pathogenic targets, including membranes of apoptotic and reactive cells. (26) As this infl ammatory marker is associated with adverse prognosis in patients with idiopathic dilated cardiomyopathy , (27,28) we investigated if levels of plasma CRP at baseline could predict outcome in patients with PPCM.…”
Section: Translational Approach From Mouse To (Wo)manmentioning
confidence: 99%